Kesehatan Mental Pada Aktivis Jama'ah Tablig Jakarta Selatan Perspektif Positive Mental Health - Ahmad Rusydi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
Not all optimistic about the results of the study of religion. Several studies assume that religion is bad for human psychological. This study would like to refute the studies. This research proves that people who follow religious activities tend to have higher mental health. The main source of this study is the Jamat activists Tabliq South Jakarta by taking a sample of 130 people. The study was conducted by analyzing the frequency distribution. Researchers also complements the data of this study with interviews regarding religious activity and everyday respondents.Keywords: Religion, Islam, Mental Health, Jamat-Tabliq